Pottery Value-Added Innovation According to the guidelines of the Integration Sufficiency Economy by Participation Communities at Banmaungnoi, Chaiyaphum Province - Pinthong, Narudom (Interdisciplinary Academic and Research Journal, 2023)
Background and Aims: Ban Mueang Noi, Chaiyaphum Province, is a village famous for producing quality pottery that has been passed down for a long time. From studying the limitations of production and marketing currently, there are only 2 types of products, namely cooking stoves, and tone only. The researcher is therefore interested in organizing the process of designing an innovative bas-relief print to increase the value of pottery in the Ban Mueang Noi community, Chaiyaphum Province, to increase the production channels for a variety of products that meet the needs of consumers in many groups, such as tourists, students, youth, etc. Examples of products include decorative ornaments, household or garden items, children’s toys, souvenirs, and souvenirs, etc. by the innovative design process of bas-relief printing that has integrated knowledge. This research is action research with objectives; (1) To study the historical context and explore problems in the production of pottery in the Ban Mueang Noi community, Chaiyaphum Province. And (2) To design an innovation to increase the value of pottery according to the Sufficiency Economy concept, integrated with the participation of the community, Ban Muang Noi, Chaiyaphum Province. Methodology: The population used in the research was a survey of 100 people in Chaiyaphum Province and 10 pottery producers. The research tools include (1) an interview with a village scholar, (2) a population opinion questionnaire, and (3) a questionnaire on satisfaction with the efficiency of pottery value-adding innovations according to the integrated sufficiency economy concept. Descriptive statistics were used to analyze the data and content analysis was used to analyze the qualitative data. Results: The research results found that; Innovative relief printing can create a variety of designs, create different products, and create another channel for producing products for the community. The innovative design process for bas-relief printing integrates the knowledge and cooperation of people in the community according to the Sufficiency Economy principle. Participation starts at the level of awareness, expressing opinions, Learning, taking action, receiving benefits, and sharing responsibility. It creates help and support, knowledge of love and unity, strengthens families and communities, promotes the economy, strengthens community relations, and preserves the good arts and culture of the local area to survive, and prosper forever. The innovation of bas-relief printing allows for a variety of product styles, and raw materials for production can be obtained locally, saving time, and allowing for mass production. The product has artistic beauty and is suitable for adding value to the pottery of the Ban Muang Noi community. Satisfaction with the efficiency of the innovation of relief printing from pottery manufacturers has a mean of 4.06, a standard deviation of 0.46. Conclusion: Low-cost, low-relief printing innovations can create a variety of products and help create alternative production channels for communities. Integration of knowledge and cooperation in the Sufficiency Economy promotes community participation and participation in promoting local culture. There is a high satisfaction from local pottery producers.